Pengaruh Psikoedukasi terhadap Ekspresi Emosi Keluarga pada Pasien Skizofrenia dalam Konteks Budaya Bugis Makassar: A Systematic Review - Muliani; Mohammad Fatkhul Mubin; Amin Samiasih; Ernawati; Siti Aisah; Nur Anna (Universitas Islam Negeri Alauddin Makassar, 2026)
Schizophrenia represents a significant global mental health challenge, with relapse rates ranging from 50% to 92%, wherein high expressed emotion within families has consistently emerged as a robust predictor of relapse across diverse cultural contexts. This systematic review synthesised existing evidence on the effectiveness of family psychoeducation in reducing negative expressed emotion amongst families caring for individuals with schizophrenia, with particular attention to cultural considerations within the Indonesian context and potential relevance to Bugis Makassar cultural values. A systematic literature search was conducted across multiple databases for publications from January 2018 to December 2025, following PRISMA guidelines. Eight quasi experimental studies from Indonesia met inclusion criteria, involving 17 to 40 families per study. All investigations demonstrated consistent positive outcomes, with psychoeducation programmes significantly reducing critical attitudes, emotional tension, caregiver anxiety, and stress levels compared with standard care. Interventions incorporating interactive methods such as group discussions or home visits showed more robust improvements in emotional regulation and family support. However, a critical gap exists regarding empirical research within specific cultural contexts such as Bugis Makassar. Theoretical alignment between psychoeducation principles and Bugis Makassar cultural values of sipakatau, sipakalebbi, and sipakainge suggests considerable promise for culturally adapted interventions. Future research should prioritise rigorous studies examining culturally grounded psychoeducation within Bugis Makassar communities to establish an evidence base for culturally appropriate mental health care delivery.